DAMPAK GAYA HIDUP MODERN IBU RUMAH TANGGA MENURUT EKONOMI ISLAM: ( Studi Kasus Desa Sadar Sriwijaya, Kec. Bandar Sribawono Kab. Lampung Timur - Afifah , Pipit; Herawati , Novita; Rahma , Aulia (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2021)
Today's society continues to be faced with things that continue to grow rapidly. All sophistication makes it easy for people to access everything they want. Over time, the current modernization process has penetrated very quickly to all corners of the world. As is the case among the community of Sadar Sriwijaya village, with the majority of the population adherents of Islamic teachings consisting of natives and immigrants, making the village always crowded. The progress of the times in the field of science and technology is well absorbed by the community, but sometimes people are less selective in responding to these changes. This study aims to determine what is the impact of the modern lifestyle of the Sriwijaya Society in the Islamic Economic Perspective?. The results show that the impact that arises with a modern lifestyle is a wasteful life, debt or crime and showing off. From some impacts it is clear that Islam is not justified, because Islam prioritizes efficiency in terms of consumption of goods and services. Basically, consumption is built on two things, namely needs and uses, Islam does not forbid a person to entertain himself because entertainment is the need of every individual, but entertainment is prohibited in Islam when entertainment is more directed to excessive fun and forgets obligations to the Almighty. and forget the people around them who need it more.